Over-the-Counter Option Market Dividend Protection and "Biases" in the Black-Scholes Model: A Note - Geske, Robert; Roll, Richard; Shastri, Kuldeep (Journal of Finance, 1983)
Robert Geske, Richard Roll, Kuldeep Shastri, Over-the-Counter Option Market Dividend Protection and "Biases" in the Black-Scholes Model: A Note, The Journal of Finance, Vol. 38, No. 4 (Sep., 1983), pp. 1271-1277